Cam Jansen and the catnapping mystery - Adler, David A.; Natti, Susanna (New York : Viking, 1998)
While visiting Aunt Molly at a fancy downtown hotel, Cam uses her photographic memory to help one of the guests find her stolen luggage and pet cat, and to catch the thief.
"Ages 7-10"--cover p. [4].
Keywords: Robbers and outlaws -- Fiction; Hotels, motels, etc. -- Fiction; Mystery and detective stories